The identification a novel gene required for lipopolysaccharide biosynthesis by Haemophilus influenzae RM7004, using transposon Tn916 mutagenesis. - High, N; Deadman, M; Hood, D; Moxon, E (1996)
Mutagenesis with the transposon Tn916 was used as a strategy to identify genes required for synthesis of the Gal alpha (1-4) beta Gal component of Haemophilus influenzae strain RM7004 lipopolysaccharide. Insertion of Tn916 into an open reading frame (ORF) encoding a protein with 75% homology to the Escherichia coli methionine related protein (Mrp) is described. Mutations in mrp resulted in loss of reactivity with monoclonal antibody (mAb) 4C4, which recognises Gal alpha (1-4) beta Gal, and expression of LPS with a different electrophoretic profile to that of wild-type RM7004. An unexpected feature of this mutation was that it appeared to influence the number of copies of 5'-CAAT-3' present in lic2A, a gene which is also required for biosynthesis and phase variable expression of the Gal alpha (1-4) beta Gal LPS epitope.